Demographic profile, production and marketing management of native pig raisers in the three largest island in the province of Romblon, Philippines - Falculan, Ken N. (Technium Social Sciences Journal, 2021)
This study was conducted to determine and evaluate production, management, marketing practices and the profitability of production of native pig raisers in the three largest island in the Province of Romblon. This study used the descriptive research design, the data gathered were statistically analyzed using frequency/percentage and mean. From the analysis and interpretation conducted it was found out that the oldest pig raisers is 73 years old, female, married, high school graduate, engage in farming with estimated monthly income of P3,000-5,000, having 3 members in the family and manage pigs through personal experience; adopted combination of fattening and breeding, with a meager capital and raised 3- 4 pigs throughout the years of raising swine; breed through natural mating and the source of boar is within the pigpen and others from rental/sharing. The pigs were fed with a combination of commercial, local and leftover feeds using a movable federer. Majority of the piggeries were located at the upland areas, tethered, tied under the tree and the pigpen was constructed at the ground; buried their carcass waste to avoid common environmental issues; and the majority of the pig raisers applied antibiotics to cure diseases in their pigs. The pig raisers always rear pigs to meet emergency household expenses; never sell pigs in terms of barter or exchange of other goods; and due to low cost requirements.